(untitled) (Journal of the Bangladesh Agricultural University, 2016)
Small heat-shock proteins (sHSPs), an abundant and ubiquitous family of molecular chaperones, can effectively prevent irreversible aggregation of non-native proteins by forming soluble complex. The CLA of sHSPs is usually determined by the capacity to suppress thermally or chemically induced protein aggregation. Various factors can effectively influence the CLA, and among them the ionic strength of the preparation and working buffer is an important factor. The study deals with the effect of ionic strength of buffer on the CLA of two silkworm sHSPs: namely sHSP19.9 and sHSP20.8 against the thermally-induced aggregation of BLC, a non-native protein. The study clearly revealed that sHSP19.9 required high ionic strength (more NaCl concentration) in reaction buffer to prevent irreversible aggregation of BLC. On the other hand, such high ionic strength condition is not necessary for sHSP20.8 but it influences the activity in some context. J. Bangladesh Agril. Univ. 12(2): 241-249, December 2014